The landscape of cell regulatory and communication networks in the human dental follicle - Liu, Jia-Ning; Tian, Jiong-Yi; Liu, Lu; Cao, Yuan; Lei, Xiao; Zhang, Xiao-Hui; Zhang, Zi-Qi; He, Jun-Xi; Zheng, Chen-Xi; Ma, Chao; Bai, Sheng-Feng; Sui, Bing-Dong; et al. (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionThe dental follicle localizes the surrounding enamel organ and dental papilla of the developing tooth germ during the embryonic stage. It can differentiate and develop to form the periodontal ligament, cementum, and alveolar bone tissues. Postnatally, the dental follicle gradually degenerates, but some parts of the dental follicle remain around the impacted tooth. However, the specific cellular components and the intricate regulatory mechanisms governing the postnatal development and biological function of the dental follicle have not been completely understood.MethodsWe analyzed dental follicles with single-cell RNA sequencing (scRNA-seq) to reveal their cellular constitution molecular signatures by cell cycle analysis, scenic analysis, gene enrichment analysis, and cell communication analysis.ResultsTen cell clusters were identified with differential characteristics, among which immune and vessel-related cells, as well as a stem cell population, were revealed as the main cell types. Gene regulatory networks (GRNs) were established and defined four regulon modules underlying dental tissue development and microenvironmental regulation, including vascular and immune responses. Cell–cell communication analysis unraveled crosstalk between vascular and immune cell components in orchestrating dental follicle biological activities, potentially based on COLLAGAN-CD44 ligand–receptor pairs, as well as ANGPTL1-ITGA/ITGB ligand–receptor pairs.ConclusionWe establish a landscape of cell regulatory and communication networks in the human dental follicle, providing mechanistic insights into the cellular regulation and interactions in the complex dental follicle tissue microenvironment.